Hippocampal Avoidance Prophylactic Cranial Irradiation using Helical Tomotherapy in Small Cell Lung Cancer - Jia-Mahasap, Bongkot; Vuthiwong, Withawat; Nobnop , Wannapha; Klunklin, Pichayaponne; Sripan, Patumrat; Chitapanarux, Imjai; Tharavichitkul, Ekkasit; Chakrabandhu, Somvilai; Onchan, Wimrak (Biomedical Sciences and Clinical Medicine, 2024)
OBJECTIVE Prophylactic cranial irradiation (PCI) is a standard treatment for small cell lung cancer (SCLC). Reduced radiation doses at the hippocampal region during PCI might protect against neurocognitive decline after radiotherapy (RT). The purpose of this study is to report the outcome of hippocampal avoidance PCI (HA-PCI) in our center. METHODS After the initial treatment of SCLC, patients whose radiographic data confirmed the absence of intracranial metastasis and controlled of the primary disease received HA-PCI. Thai Mental State Examination (TMSE) and bilateral hippocampal volumes were recorded and analyzed using the Wilcoxon Singed Rank test to compare baseline and two time points (3 and 6 months). The two-year overall survival (OS) and brain control rates were estimated using the Kaplan Meier method. RESULTS Between 2018 and 2021, a total of 10 patients were included in the analysis. The median TMSE and bilateral hippocampal volumes showed no statistically significant difference between baseline and 3 and 6 months. Two-year OS and brain control rates were 78.8% and 71.4%, respectively. Three patients developed intracranial relapses after HA-PCI which were located outside the hippocampal region. CONCLUSIONS HA-PCI did not increase intracranial relapse in this study. HA-PCI should be considered as a treatment option which can potentially protect neurocognitive functions.